2007
DOI: 10.1007/s00259-006-0356-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel 111In-labelled bombesin analogues for molecular imaging of prostate tumours

Abstract: Purpose It has been shown that some primary human tumours and their metastases, including prostate and breast tumours, overexpress gastrin-releasing peptide (GRP) (5-14)), was tested in vivo in biodistribution studies using rats bearing GRP receptor-expressing CA20948 tumours, and nude mice bearing human PC3 xenografts. Injection of 111In-labelled Cmp 3 in these animals showed high, receptor-mediated uptake in receptor-positive organs and tumours which could be visualised using planar gamma camera and micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 49 publications
3
53
0
2
Order By: Relevance
“…Therefore the development of labeled Bn analogues for imaging or targeted cytotoxicity is a very active area of investigation at present. Numerous radiolabeled [ 111 Indium, 68 Gallium, 177 Lutetium, 64 Copper, 86 Yttrium, 18 F, 99m Tc] GRP analogues with enhanced stability that bind with high affinity to BB 2 -receptors are reported, as well as there ability to image various human tumors in vivo using gamma detectors or PET imaging [10,[69][70][71][72][73][74][75][76][77]. In some preliminary studies in humans, tumors were imaged in the majority of patients, and in some cases, tumors were detected using radiolabeled Bn analogues that were not seen on other commonly used imaging modalities [75,[78][79][80].…”
Section: Iiigbb Receptors-recent Advances-tumor Imaging and Receptomentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore the development of labeled Bn analogues for imaging or targeted cytotoxicity is a very active area of investigation at present. Numerous radiolabeled [ 111 Indium, 68 Gallium, 177 Lutetium, 64 Copper, 86 Yttrium, 18 F, 99m Tc] GRP analogues with enhanced stability that bind with high affinity to BB 2 -receptors are reported, as well as there ability to image various human tumors in vivo using gamma detectors or PET imaging [10,[69][70][71][72][73][74][75][76][77]. In some preliminary studies in humans, tumors were imaged in the majority of patients, and in some cases, tumors were detected using radiolabeled Bn analogues that were not seen on other commonly used imaging modalities [75,[78][79][80].…”
Section: Iiigbb Receptors-recent Advances-tumor Imaging and Receptomentioning
confidence: 99%
“…Bn has relatively high affinity for both the BB 1 -receptor and the BB 2 -receptor, therefore many of the older pharmacological studies, both in vitro and in vivo, which usually used Bn as the agonist, provide limited information about the subtype of Bn receptor involved [3••]. Whereas BB 3 -receptor has low affinity for all natural occurring Bn-related peptides, a synthetic Bn ligand, [D-Tyr 6 , β-Ala 11 , Phe 13 , Nle 14 ] bombesin [6][7][8][9][10][11][12][13][14] , has been described [7] which has high affinity for the human and monkey BB 3 -receptor and this peptide or its analogues are being widely used to study the presence of the BB 3 -receptor, as well as other Bn receptors in human tissues by autoradiographic methods [8,9,10•]. This synthetic peptide has the unique property of having high affinity also for the BB 1 -receptor and BB 2 -receptor from all species.…”
Section: Mammalian Bn Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies in PC-3-bearing mice, 67 Ga-PESIN, 177 Lu-AMBA, and 99m Tc-demobesin-1 showed tumor uptake of 14.8, 6.4, and 16.2 %ID/g, respectively (9,(25)(26)(27)(28). Variation in amounts of peptides, mouse strain (species, sex, and weight), tumor cells (passage number, culture conditions) used, tumor size, and vascularization of the tumor may all be factors that affect tumor uptake and tumor-to-non-tumor ratios.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that 123I-PD153035 are promising candidates as an imaging probe for EGFR-positive prostate cancer and warrant further in vivo validations to ascertain their potential as imaging agents for clinical used. Another radiolabeled bombesin (a target molecular with high affinity for GRP receptors) analogues was synthesized and assessed for SPECT (111In label) and PET (64Cu or 18F label) visualization of prostate cancer [58,59]. However, imaging of the GRP receptor is being under the further investigation to determine whether it is useful or not in clinical trial for prostate cancer.…”
Section: Other Probes For Imaging Prostate Cancer Based On Egf Receptmentioning
confidence: 99%